A situação residencial da Nova Classe Média na metrópole do Rio de Janeiro: uma contribuição ao debate - Michael Chetry (Confins)
For the last few years, in Brazil as in other developing countries (China, India, Russia), the public debate has been mainly focused on the idea of an emerging "New Middle Class" as a result of economic growth and labor market improvements. Initially formulated by economists that identify social classes based on the unique criteria of income, this "New Middle Class" thesis is strongly criticized by the defenders of a sociological standpoint, who consider that there are no proven connections between income level and social status. The purpose of this article is to contribute to discussing this trend from a geographical perspective by focusing on the spatial dimension of the New middle class. More specifically, our study of Rio de Janeiro metropolis highlights, at least from a spatial viewpoint, that the “middle” qualification in New middle class must be put into perspective, households in this group being closer to the working class in terms of location and housing conditions.